Former students of Hjallastefnan and their leadership self-perceptions - Helga María Finnbjörnsdóttir 1980- (2014)
This thesis is meant to shed light on how former students of Hjallastefnan in Iceland, perceive their own leadership styles and whether they evaluate themselves to be more transformational leaders than individuals of the same age that attended other preschools. To the researcher´s best knowledge, no research has been conducted in Iceland to understand whether different approaches in preschool education affect leadership self-perceptions later in life. The leadership approach used in the analysis is The Full Range of Leadership Model proposed by Avolio and Bass (2004) and the measure used was the Multifactor Leadership Questionnaire (2004). Responses were collected from former students of Hjallastefnan and a comparison group, resulting in a total of 78 responses. Few significant results were found but results did give indication that former students of Hjallastefnan do neither perceive themselves as more transformational nor transactional leaders than others. However, these results must be interpreted with caution, due to the small size of the comparison group. The research also gives recommendations for possible future studies in the field of leadership and preschool education. Keywords: Transformational leadership, Hjallastefnan, Early education, Iceland, Gender differences